Experimental Evidence of the Impact of Increasing Auditors' Legal Liability on Firms' New Investments - YU, HUNG-CHAO (Contemporary Accounting Research, 2001)
This laboratory market study examines the potential effect of increasing auditors' liability on firms' new investments. The experimental hypotheses are derived from Shibano's 2000 model, which predicts that an increase in auditors' liability will decrease the frequency of audit failures and may decrease firms' new investments if the liability level is “excessive”. Results from three experimental market settings (with low, medium, and high liability levels) suggest two major conclusions. First, firms' new investments increase significantly when auditors' liability level increases from low to medium, and decrease significantly as the liability level increases from medium to high. This result provides support for the argument that adequate auditor liability is necessary to motivate firms to invest in new projects. Excessive liability, however, may discourage firms from making new investments. Second, the frequency of audit failure decreases insignificantly when auditors' liability increases. These two results have an important policy implication: the benefit of imposing high liability on the auditor (i.e., an insignificant decrease in audit failure) may be more than offset by its cost (i.e., a significant decrease in new investments).